The employer’s duty to provide labor protection in Ukraine - Ruslan I. Kovalenko, Mykola I. Inshyn, Olena V. Moskalenko,; Dashutin, Igor V.; Hanechko, Olena M. (Opción, 2019)
This paper aims to improve the doctrine of labor protection, its legal regulation in view of the employer’s obligation to ensure safe and healthy working conditions. The obtained results can be used as a basis for further research by the Institute of labor protection. The conclusions, suggestions, and recommendations can be used in the process of improving the labor legislation of Ukraine. The results might be helpful for increasing the level of labor protection efficiency at enterprises, institutions, organizations as well as at educational institutions (to improve the educational and methodological content of disciplines).